Os efeitos da mídia sobre o suicídio: Uma análise empírica para os estados brasileiros - Paulo R. A. Loureiro; Tito Belchior Moreira; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Using data for the 27 Brazilian states during the period 1980-2009, we found that the media index in an important determinant of the suicide rates. The econometric results suggest that an increase of 1% in the media index increases the suicide rate for young males (age between 15 and 29 years old) in 5.34%. Suggesting that contagion plays a particularly important role in teen suicide, which reinforces the results obtained by Cutler, Glaeser e Norberg (2001). Furthermore, we found that both unemployment and violence impact positively in the suicide rates.
Keywords: C23; D03; D69; I15; K14; 330; media contagion; unemployment; panel data; youth suicide